Implementasi Kebijakan Badan Usaha Milik Desa ( BUMDes ) Di Desa Pruwatan Kecamatan Bumiayu Kabupaten Brebes - khamadi, abdulloh; sutikno, chamid; pribadi, indah ayu permana (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The establishment of BUMDes basically aims to increase village productivity and ultimately improve the community's economy. The existence of BUMDes in villages, if managed well, can also contribute to a large increase in Village Original Income (PADes), including in the Pruwatan Village area, Bumiayu District. This research aims to analyze the implementation of Village-Owned Enterprises (BUMDes) policies in Pruwatan Village, Bumiayu District, Brebes Regency. Descriptive qualitative methods are used to describe the implementation of Village-Owned Enterprise (BUMDes) policies. The research was conducted in Pruwatan Village, Bumiayu District, Brebes Regency. The selection of informants was carried out using a purposive sampling technique, with 5 informants selected from various elements who were considered to have knowledge about the implementation of Village-Owned Enterprise (BUMDes) policies. This research focuses on one research focus, namely the implementation of Village-Owned Enterprises (BUMDes) policies in Pruwatan Village. Data collection uses observation, interviews and documentation. The type of data used in this research is primary data obtained from interviews with research informants and secondary data in the form of reports and official documents Based on the results of the study, it can be seen that the implementation of the policy refers to the theory put forward by Edward III, that it has not run optimally, this can be seen from the lack of coaching and guidance, the level of ineffective communication and the lack of community participation.